2001
DOI: 10.1074/jbc.m009375200
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Differentially Spliced Carboxyl Terminus in Thromboxane A2 Receptor Trafficking

Abstract: The thromboxane A 2 receptor (TP) is a G protein-coupled receptor that is expressed as two alternatively spliced isoforms, ␣ (343 residues) and ␤ (407 residues) that share the first 328 residues. We have previously shown that TP␤, but not TP␣, undergoes agonist-induced internalization in a dynamin-, GRK-, and arrestindependent manner. In the present report, we demonstrate that TP␤, but not TP␣, also undergoes tonic internalization. Tonic internalization of TP␤ was temperature-and dynamin-dependent and was inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(139 citation statements)
references
References 36 publications
8
131
0
Order By: Relevance
“…Our work provides experimental evidence to support their proposal. Such regulatory phenomenon is however not a unique property of CB 1 R, as similar differences in the mechanisms of tonic versus agonist-induced internalization have been demonstrated in the case of other GPCRs, such as the TP thromboxane A2 receptor (Parent et al, 2001), the Y1 neuropeptide Y receptor (Holliday et al, 2005) or the mGlu 1 metabotropic glutamate receptor (Dale et al, 2001). Furthermore, we also show here that the spontaneous internalization of CB 1 R is not simply a consequence of its constitutive activity, since it also occurs in the presence of the CB 1 R inverse agonist AM251, i.e.…”
Section: Discussionmentioning
confidence: 69%
“…Our work provides experimental evidence to support their proposal. Such regulatory phenomenon is however not a unique property of CB 1 R, as similar differences in the mechanisms of tonic versus agonist-induced internalization have been demonstrated in the case of other GPCRs, such as the TP thromboxane A2 receptor (Parent et al, 2001), the Y1 neuropeptide Y receptor (Holliday et al, 2005) or the mGlu 1 metabotropic glutamate receptor (Dale et al, 2001). Furthermore, we also show here that the spontaneous internalization of CB 1 R is not simply a consequence of its constitutive activity, since it also occurs in the presence of the CB 1 R inverse agonist AM251, i.e.…”
Section: Discussionmentioning
confidence: 69%
“…Both TPα and TPβ have recently been established to undergo agonist-induced homologous desensitization and phosphorylation in transfected HEK 293 cells [96]. In addition, recent studies indicate that TPβ, but not TPα, may undergo agonist-induced internalization [97,98] and we have established that the TP isoforms are subject to differential prostanoid EP 1 receptor-induced desensitization mediated at PKC sites unique to the individual TPs [63].…”
Section: Tp Receptor Desensitizationmentioning
confidence: 62%
“…Carpentier et al concluded, that F229V mutation does not increase constitutive internalization of the receptor, although only receptor/β-arrestin and β-arrestin/AP2 interaction were measured with dominant negative dynamin or agonist treatment, and it was not shown whether the inverse agonists could affect the cell surface expression of the mutant (11). The dissimilarity in the agonist induced and constitutive internalization observed in this study in case of I130N-V2R is not unique among GPCRs, since β-arrestin-dependent, agonist-induced endocytosis and β-arrestin-independent constitutive internalization was introduced earlier (22)(23)(24). It is also notable, that basal internalization is not obviously a consequence of constitutive activity (25).…”
Section: Discussionmentioning
confidence: 98%